Laboratory Evaluation of the Formosan Subterranean Termite Resistance of Borate-treated Rubberwood Chipboard - Wong, Andrew H.H; J. Kenneth, Grace (IRGWP, 2004)
Both no-choice and two-choice 4-week AWPA laboratory tests were performed to evaluate the resistance of borate-treated rubberwood (Hevea brasiliensis) chipboard prepared from a commercial mill run, against the Formosan subterranean termite Coptotermes formosanus. Boric acid (technical granular) was incorporated into the boards during manufacture to achieve loadings of 1.0% or 1.1% boric acid equivalents (BAE). In the no-choice test, both the untreated chipboard and solid rubberwood controls sustained heavy termite attack (respective mean visual ratings of 4.6 and 2.7 on a 10- point AWPA scale), while the two retentions of borate-treated chipboard showed only light grazing (mean rating 9.2). The two-choice test demonstrated a preference of termites for solid rubberwood (mean rating 2.4) instead of untreated chipboard (rating 8.4), and for untreated (mean rating 8.4 and 8.8) instead of borate-treated (mean ratings 9.8 & 9) chipboards. Complete termite mortality in the presence of borate-treated chipboard in both laboratory tests demonstrates the toxicity of borates to Formosan subterranean termites.